Preconcentration of Cr (VI) Using Ca-Alginate-EDTA Microcapsules in a Column System for UV-Vis Spectrophotometric Analysis - Ika Yekti Lianasari; Aman Sentosa Panggabean; Resma Lita Farlianti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2025)
This study introduces optimized Ca-Alg-EDTA microcapsules specifically designed as a high-performance column filler for the preconcentration and sensitive detection of toxic Cr(VI) in aquatic systems. Monitoring Cr(VI) at trace levels is critical due to its high toxicity and environmental persistence. Unlike previous alginate-based sorbents, this work focuses on a synergistic EDTA integration within a column-switching framework to enhance retention efficiency (74.73 %) and capacity (0.3995 mg/g). Analytical validation using UV-Vis spectrophotometry demonstrated excellent linearity (R2 = 0.9995) with a low detection limit of 0.014 mg/L, ensuring reliability for samples with minimal analyte concentrations. The method’s robustness was confirmed through Mahakam River water analysis, yielding a 93.05 % recovery in compliance with AOAC 2002 standards. This optimized microencapsulation approach provides a cost-effective and sustainable solution for routine environmental monitoring of heavy metal contamination.